(untitled) (Innovaciones Educativas, 2025)
This essay aims to present the relationship between educational and community management within the framework of Costa Rican policy, based on the school’s operations. In this sense, it addresses the principles that converge between the school and its environment; the collaborative and dynamic processes carried out in their interaction to develop and lead joint plans on common issues; furthermore, the interconnection with policy and its contributions to reorienting the management of the school and its surroundings. In conclusion, education, its link with the community, and regulations form an interconnection network that develops capabilities in the participants and creates greater dynamism in self-management processes, to improve and enhance individual, institutional, and social life endeavors. Thus, policy empowers and guides the school in creating collaborative projects; community management enriches the curriculum and intercultural processes within the classrooms; and educational management strengthens its capacity to act to contribute to quality and the transformation of its own reality in response to the country’s interests and the demands of today’s society.